Costing, budgeting and controlling models to improve the public sector (Costos y Gestión, 2024)
The tendency for government to grow is a hallmark of modernity. Current trends and future perspectives on public spending do confirm that cost increases will stay for long.In this scenario, adequate techniques and tools are needed to develop results-oriented public policies in order to achieve politically established goals through effective decisions and actions for public sector good management benefiting societies all over the world.This article goal is to introduce the concepts of costing models, budgeting methodologies, performance evaluation and control tools through specific methodologies based on real recent world evidence and case studies in different countries. Tools that help face this challenge are key to success (for worldwide societies): activity-based costing and activity-based management, zero-based budgeting and control tools have proven to be useful in this continuous journey, being New Public Management or Bureaucratic models, the schemes used to run states at country, province or city levels.
Keywords: public management; costs; budget; control